SMART Recovery: Continuing Care Considerings for Rehabilitation Counselors. (July 2015) - O'Sullivan, Deirdre; Blum, Jillian B.; Watts, Justin; Bates, Julie K.
Peer support groups are the most utilized form of treatment for individuals recovering from substance abuse and substance dependence. This study examined an understudied peer support program (Self-Management and Recovery Training [SMART] Recovery), which is distinct from traditional 12-step models. Although treatment planning for substance use disorders is not the primary focus of vocational rehabilitation (VR), persons with disabilities are at increased risk for these disorders. Due to the bio-psycho-social nature of substance use disorders, VR counselors must consider ethical treatment recommendations for clients who demonstrate need for supplemental treatment. This descriptive-survey study investigated two samples of member and facilitator characteristics, motivations, and recovery goals among the SMART Recovery community. Implications for VR counselors making best practice recommendations for clients with substance use disorders are discussed.